Consensus Statement on Perioperative Use of Neuromuscular Monitoring. (July 2018) - Naguib, Mohamed; Brull, Sorin J.; Kopman, Aaron F.; Hunter, Jennifer M.; Fülesdi, Béla; Arkes, Hal R.; Elstein, Arthur; Todd, Michael M.; Johnson, Ken B.
Abstract : A panel of clinician scientists with expertise in neuromuscular blockade (NMB) monitoring was convened with a charge to prepare a consensus statement on indications for and proper use of such monitors. The aims of this article are to: (a) provide the rationale and scientific basis for the use of quantitative NMB monitoring; (b) offer a set of recommendations for quantitative NMB monitoring standards; (c) specify educational goals; and (d) propose training recommendations to ensure proper neuromuscular monitoring and management. The panel believes that whenever a neuromuscular blocker is administered, neuromuscular function must be monitored by observing the evoked muscular response to peripheral nerve stimulation. Ideally, this should be done at the hand muscles (not the facial muscles) with a quantitative (objective) monitor. Objective monitoring (documentation of train-of-four ratio ≥0.90) is the only method of assuring that satisfactory recovery of neuromuscular function has taken place. The panel also recommends that subjective evaluation of the responses to train-of-four stimulation (when using a peripheral nerve stimulator) or clinical tests of recovery from NMB (such as the 5-second head lift) should be abandoned in favor of objective monitoring. During an interim period for establishing these recommendations, if only a peripheral nerve stimulator is available, its use should be mandatory in any patient receiving a neuromuscular blocking drug. The panel acknowledges that publishing this statement per se will not result in its spontaneous acceptance, adherence to its recommendations, or change in routine practice. Implementation of objective monitoring will likely require professional societies and anesthesia department leadership to champion its use to change anesthesia practitioner behavior.